2021
DOI: 10.1098/rsos.201652
|View full text |Cite
|
Sign up to set email alerts
|

Screening of anti-Acinetobacter baumanniiphytochemicals, based on the potential inhibitory effect on OmpA and OmpW functions

Abstract: Therapeutic options including last-line or combined antibiotic therapies for multi-drug-resistant strains of Acinetobacter baumannii are ineffective. The outer membrane protein A (OmpA) and outer membrane protein W (OmpW) are two porins known for their different cellular functions. Identification of natural compounds with the potentials to block these putative porins can attenuate the growth of the bacteria and control the relating diseases. The current work aimed to screen a library of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Based on the fact that a drug-like molecule is that which possesses sufficiently acceptable pharmacokinetic (PK) properties and a good ADMET profile [ 76 , 77 ], the physicochemical properties of the benzimidazole-thiosemicarbazone hybrids under study (listed in Tables 1 and 2 ) were computed. The PK parameters important for good in vivo activity of a drug include its systemic exposure (dependent on absorption, distribution, metabolism, and excretion), its bioavailability (dependent on absorption and metabolism), and its elimination from the body (dependent on metabolism, distribution, and excretion) [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the fact that a drug-like molecule is that which possesses sufficiently acceptable pharmacokinetic (PK) properties and a good ADMET profile [ 76 , 77 ], the physicochemical properties of the benzimidazole-thiosemicarbazone hybrids under study (listed in Tables 1 and 2 ) were computed. The PK parameters important for good in vivo activity of a drug include its systemic exposure (dependent on absorption, distribution, metabolism, and excretion), its bioavailability (dependent on absorption and metabolism), and its elimination from the body (dependent on metabolism, distribution, and excretion) [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…In all cases, the predicted fraction unbound to plasma proteins is low (Fu < 5%). Note that Fu affects the volume of distribution and potency because only unbound (free) drugs can diffuse across cell membranes from plasma to the tissues [ 77 , 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, docking studies and the effects of specific inhibitors have identified both OmpA and OmpW as potential targets for drug development against A . baumannii infections [ 13 , 38 , 39 ]. Given its important role in transport of essential nutrients, OmpW has also been shown to be a highly immunogenic protein and a candidate for the development of an effective vaccine to control A .…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, molecular docking results have shown that resorcinol, paracresol, 3‐methyl‐2‐cyclopenten‐1‐one (−6.705, −6.243, −6.191 kcal/mol, respectively) from B. polymorpha are top three ligands to interact with the selected binding pocket of OmpA (Figure 5). Shahryari et al (2021) have reported the potential of flavonoid compounds to inhibit the function of OmpA in Acinetobacter baumanii which causes hospital acquired infections. Many works summarizing the structure and functions of OmpA have emphasized on the feasibility of using OmpA as a potential therapeutic target.…”
Section: Resultsmentioning
confidence: 99%
“…Flexibility of the backbone was evaluated using RMSF plots. Higher RMSF value means the higher flexibility while the lower value represents the lower mobility during simulation (Shahryari et al, 2021). The plots for 10,000 ps trajectories of simulation have revealed that the RMSF were in the range of 0.1–0.5 nm for all the receptors (Figure 6c,d).…”
Section: Resultsmentioning
confidence: 99%